Analisis Manajemen Pelayanan Publik Lintas Agama dan Tata Kelola Kepegawaian: (Studi Kolaboratif Magang Mahasiswa UIN Sumatera Utara di Kemenag Kota Medan) - Annisa Ulfa Andriani; Sahdin Hasibuan; Widia Lestari; Nurul Fitriyani; Indana Sephia Citra (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
This internship program aimed to provide practical experience for students from Universitas Islam Negeri Sumatera Utara in understanding public service management across religious communities and personnel governance within government institutions. The internship took place at the Office of the Ministry of Religious Affairs of Medan City, an institution playing a strategic role in delivering religious services and managing civil servants. The main focus of this study was on cross-religious public services and the implementation of personnel management systems. The findings indicate that the Ministry of Religious Affairs of Medan City applies principles of fairness, tolerance, and professionalism in delivering cross-religious public services, supported by an organized and structured personnel governance system. This internship offers significant benefits to students by enhancing their practical knowledge, administrative skills, and professional attitudes, especially in handling diversity within the public sector. By experiencing the management of public services and personnel governance, students gained valuable insights into the operational challenges and strategies employed in the public administration of religious affairs.